2009
DOI: 10.1111/j.1751-908x.2009.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Isotopes (δ44/40Ca) in MPI‐DING Reference Glasses, USGS Rock Powders and Various Rocks: Evidence for Ca Isotope Fractionation in Terrestrial Silicates

Abstract: We report δ44/40Ca(SRM 915a) values for eight fused MPI‐DING glasses and the respective original powders, six USGS igneous rock reference materials, the U‐Th disequilibria reference material TML, IAEA‐CO1 (Carrara marble) and several igneous rocks (komatiites and carbonatites). Sample selection was guided by three considerations: (1) to address the need for information values on reference materials that are widely available in support of interlaboratory comparison studies; (2) support the development of in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
126
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(154 citation statements)
references
References 43 publications
26
126
2
Order By: Relevance
“…They advocated that the Ca isotopic effects be reported relative to the bulk silicate Earth (BSE). However, several recent studies show that at a 2r level of 0.5 e units, NIST SRM 915a and seawater do not show any measurable radiogenic 40 Ca excess compared to the Earth's mantle (e.g., Amini et al, 2009;Caro et al, 2010; Table 1). Therefore, in this study NIST SRM 915a is used as the standard sample for reporting both mass-dependent and mass-independent Ca isotopic effects (Eqs.…”
Section: Reporting Of Ca Isotopic Effectsmentioning
confidence: 95%
“…They advocated that the Ca isotopic effects be reported relative to the bulk silicate Earth (BSE). However, several recent studies show that at a 2r level of 0.5 e units, NIST SRM 915a and seawater do not show any measurable radiogenic 40 Ca excess compared to the Earth's mantle (e.g., Amini et al, 2009;Caro et al, 2010; Table 1). Therefore, in this study NIST SRM 915a is used as the standard sample for reporting both mass-dependent and mass-independent Ca isotopic effects (Eqs.…”
Section: Reporting Of Ca Isotopic Effectsmentioning
confidence: 95%
“…The latter exhibit such a narrow range of d 44/40 Ca values, however, that it must be the carbonate rocks that control secular changes in d T w . For example, seven analyses of rocks of basaltic to andesitic composition, reported by Amini et al (2009), exhibit a total range of variation of just 0.16& at the 95% level of confidence, and an average d 44/40 Ca value of À1.06&.…”
Section: The Role Of Sgd In the Global Ca-cyclementioning
confidence: 96%
“…It has been suggested that other dietary calcium inputs may come through the use of soft carbonate millstones for the preparation of flour from grains (Heaney, 2002); however, this again would provide a calcium input with a high 44 Ca/ 42 Ca isotope ratio (Tipper et al, 2008;Amini et al, 2009), so does not provide an explanation for low human d 44/42 Ca values.…”
Section: Dairy and Bone Consumptionmentioning
confidence: 96%
“…This means that the calcium isotope ratios within a restricted area only should be compared to each other in assessing other effects such as the trophic level. We account for this difference by the small variability in calcium isotope ratios between rock types (Amini et al, 2009;Holmden, 2009), biogeochemical cycling in different ecosystems (see for example Holmden and Belanger, 2010), and differences in rock weathering (Moore et al, 2009).…”
Section: Archaeological Samplesmentioning
confidence: 99%
See 1 more Smart Citation